Severe cutaneous adverse reactions to anti-osteoporosis drugs: a real-world pharmacovigilance study using the FDA Adverse Event Reporting System database and a review of published cases - Li, Jun-Wei; Lei, Xin-Dong; Dai, Bing (Frontiers in Pharmacology, 2025)
ObjectiveThis study analyzed severe cutaneous adverse reactions (SCARs) linked to anti-osteoporosis drugs using FDA Adverse Event Reporting System (FAERS) data and characterized implicated drugs and clinical features through a literature review.MethodsA retrospective disproportionality analysis of SCAR reports from FAERS (2004–2024) utilized signal detection metrics, including reporting odds ratio (ROR), proportional reporting ratio (PRR), and Bayesian confidence propagation neural network (BCPNN). A structured literature search across PubMed, Web of Science, and Scopus gathered case reports of SCARs induced by anti-osteoporosis drugs.ResultsOf 77,789 SCAR reports, 399 (0.51%) involved anti-osteoporosis drugs, mainly affecting female patients (76.25%) with a median age of 69 years. Denosumab (24%), alendronate (23.25%), and zoledronic acid (17.13%) were most frequently reported. Significant signals included risedronic acid with erythema multiforme [ROR = 9.06; PRR = 9.03; information component (IC) = 3.17], zoledronic acid with cutaneous vasculitis (ROR = 3.15; PRR = 3.15; IC = 1.65), and alendronic acid with Stevens–Johnson syndrome (SJS) (ROR = 4.03; PRR = 4.02; IC = 2.00). The literature review (33 cases) confirmed a median symptom onset of 22 days, with treatments often involving corticosteroids and supportive care.ConclusionAnti-osteoporosis drugs, notably bisphosphonates and strontium ranelate, are rarely linked to SCARs but may cause serious consequences. Increased clinical awareness, pre-treatment risk evaluation, and vigilant monitoring are essential for at-risk patients.